Magneto-optical spectroscopy of d- and f-ferromagnetic materials: recent theoretical progress - Antonov, V.N.; Yaresko, A.N.; Perlov, A.Ya.; Nemoshkalenko, V.V. (Физика низких температур, 1999)
The current status of theoretical understanding of the optical and magneto-optical (MO) spectra of 3d, 4f and 5f compounds is reviewed. Energy band theory based upon the local spin-density approximation (LSDA) describes the optical and MO spectra of transition metal compounds reasonably well. Examples which we examine in detail are XPt₃ compounds (with X= 3dV, Cr, Mn, Fe, and Co) in the AuCu₃ structure, ternary Heusler alloys NiMnSb, PdMnSb, PtMnSb, and MnBi compound. The LSDA, which is capable of describing the spectra of transition-metal alloys with high accuracy, does not suffice for lanthanide compounds having a correlated 4f shell. A satisfactory description of the optical spectra could be obtained by using a generalization of the LSDA, in which explicitly f electron Coulomb correlations are taken into account (LSDA+U approach). As examples of this group we consider CeSb and CeBi. For CeSb a record Kerr angle of 90╟ was very recently reported, 90╟ is the absolute maximum value that can be measured. It is two orders of magnitude larger than the values that are commonly measured for transition-metal compounds, and about one order of magnitude larger than values maximally achieved for other lanthanide and actinide compounds. A third group consist of uranium 5f compounds. In those compounds where the 5f electrons are rather delocalized, the LSDA describes the MO spectra reasonably well. As examples of this group we consider UAsSe and URhAl. Particular difficulties occur for the uranium compounds where the 5f electrons are neither delocalized nor localized, but more or less semilocalized. Typical examples are US, USe and UTe. The semilocalized 5f`s are, however, not inert, but their interaction with conduction electrons plays an important role. Recently achieved improvements for describing such compounds are discussed.